A review on chemical profiles and biological activities of essential oil from some plants belonging to family Scrophulariaceae - Luu, Thao Nguyen; Van, Hong Thien (Plant Science Today, 2022)
Scrophulariaceae is a large family, many species of which have been reported to have a wide range of biological activities and uses as folk medicines. The essential oils from species belonging to this family mainly contain monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, oxygenated sesquiterpenes and non-terpenes. Furthermore, their essential oils have been reported to have a variety of biological activities such as antimicrobial, antioxidant, insecticidal etc. The objective of this review is to provide a brief overview of the chemical composition and biological activities of the essential oils isolated from different parts of species included in the Scrophulariaceae family. In addition, this paper also introduces the therapeutic potentials and provides the evidence for future medicinal applications of those species.